IMPLEMENTING GROUP INVESTIGATION MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT GRADE IV SD NEGERI 091305 PERSATUAN BARU - Murdiono Lumban Gaol; Ester Julinda Simarmata; Regina Sipayung; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The results of this study indicated that implementing Group Investigation model increased students’ learning outcomes. It was seen from the improvement of students’ learning outcomes in each cycle. Before implementing the Group Investigation model, the result of the initial test (pretest) showed that 5 students (20%) reached the learning target, while 20 students (80%) did not reach the learning target with an average score of 56. Then, the observation in cycle I obtained that teachers’ activities was 62% while the students’ activities was 56%. Moreover, it was found that in cycle I, 10 students (40%) reached the learning target and 15 students (60%) did not reach the target score. The average score in this cycle was 67,52. This result implied that in general, 75% of the students did not yet achieve the target score; thus, the study was proceeded on cycle II. In cycle II, the observation results indicated that the teacher’s activities was 80% while the students’ activities was 82%. After that, the result of students’ learning outcome showed that 21 students (84%) reached the learning target, while 4 students (16%) did not reach the learning target, and the average score was 79,72. Based on the data analysis, it was concluded that implementing Group Investigation model improved students’ learning outcomes.